1986
DOI: 10.1203/00006450-198611000-00100
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Growth-Hormone - Releasing Hormone (Grf) in 5 Children With Impaired Growth Hormone (Gh) Secretion

Abstract: Because pituitary GH release is inhibited by GIH and hypothalamic secretion of this peptide seems to be mainly dependent on 8-adrenergic regulation,we have investigated if BAB could modify the pattern of GH response to GRF-29 in 5SN (3V,2F;7.8-9.6 y) and 5IGH-D (4M,lF;6.3-12.7).Blood samples for GH where collected from-15'to+ 60'according the following tests:' A)Propranolol(1 mg/kg,as iv bolus at-6O');B)GRF(l mcg/kg,as iv bo- .

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1987
1987
1995
1995

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…GRF as a therapeutical agent has proven to be effective in promoting linear growth in GH-deficient children when administered by an infusion pump [10,11], but the effect of subcutaneous administration is not yet clearly documented [12][13][14][15], The aim of our study was to investigate which dosage, ad ministered once a day subcutaneously, would be suitable to increase growth. A fur ther aim was to investigate this in a mini mum period of time, in order to restrict the burden to the patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…GRF as a therapeutical agent has proven to be effective in promoting linear growth in GH-deficient children when administered by an infusion pump [10,11], but the effect of subcutaneous administration is not yet clearly documented [12][13][14][15], The aim of our study was to investigate which dosage, ad ministered once a day subcutaneously, would be suitable to increase growth. A fur ther aim was to investigate this in a mini mum period of time, in order to restrict the burden to the patients.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that a considerable propor tion of adults and children with GH defi ciency show an increase of plasma GH in response to an intravenous GRF bolus, which has been interpreted as an indication that in these cases the GH deficiency is of hypothalamic origin [3][4][5][6][7][8], On the other hand, a negative GH response to GRF does not exclude a hypothalamic origin, as prim ing the pituitary with repeated GRF boluses can increase the GH response [9], Theoretically, GRF could be used as a therapeutical agent in GH deficiency of hy pothalamic origin. This was confirmed for GRF administered every 3 h by intravenous and subcutaneous infusion [10,11], Later, GH-deficient children were treated with one or two subcutaneous injections daily by var ious investigators, but the results were quite variable [12][13][14][15], At present, it has not been firmly established which dosage and which frequency of administration leads to results which are as good as these of GH therapy. In addition, not all GH-deficient children re spond favourably, even when only those children are selected who show a clear GH response to the diagnostic intravenous GRF test.…”
Section: Introductionmentioning
confidence: 97%